2015
DOI: 10.1097/inf.0000000000000556
|View full text |Cite
|
Sign up to set email alerts
|

Similar Proportions of Stool Specimens From Hospitalized Children With and Without Diarrhea Test Positive for Clostridium difficile

Abstract: C. difficile PCR assays are frequently positive in hospitalized children both with and without diarrhea. As we observed a high level of toxigenic C. difficile colonization in children, our findings suggest that a positive C. difficile PCR result in a child with diarrhea should be interpreted with caution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
39
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 29 publications
2
39
0
Order By: Relevance
“…While the detection of toxigenic organisms may be appropriate for determining the need for infection control measures (45), it is not necessarily optimal for deciding whether or not toxigenic C. difficile is the cause of a patient's symptoms (16). Notably, multiple studies have reported NAAT-positive individuals who clinically did not have CDI (12,(15)(16)(17)(18). Until now, no highly sensitive assay existed that could rapidly detect and quantify both toxins A and B in stool samples at the time of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the detection of toxigenic organisms may be appropriate for determining the need for infection control measures (45), it is not necessarily optimal for deciding whether or not toxigenic C. difficile is the cause of a patient's symptoms (16). Notably, multiple studies have reported NAAT-positive individuals who clinically did not have CDI (12,(15)(16)(17)(18). Until now, no highly sensitive assay existed that could rapidly detect and quantify both toxins A and B in stool samples at the time of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Despite arguments that the detection of toxin in stool has highest clinical specificity and predictive value (2,11,12,14), nucleic acid amplification testing (NAAT) for ultrasensitive detection of toxigenic organisms is increasingly employed for diagnosis. However, studies have repeatedly reported on NAAT-positive individuals who clinically would not be diagnosed with CDI (12,[15][16][17][18]. Thus, by detecting C. difficile organisms, rather than toxins A and B, NAAT may lack specificity for clinical disease (2).…”
mentioning
confidence: 99%
“…Using PCR for C. difficile detection in hospitalized patients with and without diarrhea, Leibowitz et al found that there was no statistically significant difference between the positivity rates of asymptomatic and symptomatic children (24% versus 19% of samples, respectively) (20). Pediatric oncology patients may also be colonized or have prolonged shedding following or in conjunction with diarrhea (21).…”
mentioning
confidence: 99%
“…Asymptomatic colonization in the community is lower than in the health-care setting and is in the range of 2-4%. Several studies report high carriage rates (25-35%) in children in the first year; the rate drops (to 15%) for ages 1-8 years [182][183][184] . This variation is probably associated with the unstable intestinal microbiota in the first 2-3 years of life, which enables C. difficile to remain established in the intestinal tract 185 .…”
Section: Asymptomatic Carriagementioning
confidence: 99%